PENGARUH PENGAWASAN, KESEHATAN DAN KESELAMATAN KERJA TERHADAP MOTIVASI DAN KINERJA KARYAWAN PADA PT. SAWIT INTI RAYA KEC. BATANG GANSAL KABUPATEN INDRAGIRI HULU - Payakun Arianzah; Nuryanti '; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to know how the influence of monitoring, health and safety to motivation and performance at PT. Sawit Inti Raya Kecamatan Batang Gansal Indragiri Hulu. The population in this study were all employees who work in the company of 102 employees. While the sampling was done by making all employees in the sample. Analysis of the data used is descriptive analysis with quantitative analysis tools that multiple linear regression with SPSS version 18.00. From the testing that has been done shows that supervision and motivation Work directly significant effect on employee performance. Health and safety at work does not affect the performance. There is no direct influence Surveillance and Health and safety at work the Employee Performance through employee motivation. Expected to companies in order to increase the sense of love / happy employees to work undertaken for example by delivering good work, facilities and infrastructure that support and nurture employees to ensure their basic needs such as providing with the compensation, allowances, incentives and other things that can trigger motivation employees in the work. With that employees will feel heavy for leaving the compan. For example by paying attention job satisfaction and organizational commitment to be more motivated employees to get more maximal perfomanceKeyword : Monitoring, Health and Safety, Motivation and Performance.